Profile of Traffic Accident Victims at RSUP Dr. M. Djamil Padang in 2010-2020 - Muhammad Irfan Pratama; Noverika Windasari; Nur Afrainin Syah; Rika Susanti; Noverial Noverial; Mohammad Reza (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
A traffic accident is an unexpected road event involving a vehicle with or without other road users resulting in human casualties and/or property loss. This research is a retrospective descriptive using secondary data from visum et repertum results of patients. The research sample was analyzed using a univariate approach to determine the distribution of age, gender, occupation, location of injuries, type of injuries, number of injuries based on the type of injury, the status of road users, and how patients arrive. The results of the study obtained as many as 2984 victims alive and 210 victims died. The age group of 15–29 years is the most (49.3% for living victims and 39% for dead victims), with a male predominance. The head and neck were the most common locations for injuries (73.1% of living victims and 90.5% of deaths). Abrasions were the most type of wound (82.4% of living victims and 81.4% of deaths). In the group of road users, 59.2% were motorbike riders and 71.1% came to the third referral hospital in Padang by being referred from another hospital. The living and dead victims due to traffic accidents based on age, gender, location of injuries, and types of injuries are in the same group.